(untitled) (Eastern Medical College Journal, 2022)
Background- Cigarette smoking is one of the common addictions. The effects of cigarette smoking on health are serious and, in many cases, deadly. Objectives: The present study was carried to observe the effect of smoking on Red Blood Cells (RBC) count, Hemoglobin (Hb) concentration, Hematocrit (HCT) and Red cell indices in adult male smokers and compare it with non-smokers to create awareness. Materials and Methods: In this study 50 adult male smokers and 50 adult male non-smokers aged from 20-45 years were taken. The smokers were regularly smoking for at least one year. Fresh peripheral blood sample from subjects were collected and analyzed for Red blood cell count, Hemoglobin concentration, Hematocrit and Red cell indices by using Mythmic-22 automated 5-part Hematology Analyzer. Result: In this study the values of RBCs count, Hb concentration and Hematocrit showed significant increase (p<0.05) in smokers as compared to non-smokers. The values of Red cell indices (MCV, MCH, MCHC) were statistically not significant between two groups. Conclusion: This study concluded that smoking causes persistent state of hypoxia in the body due to smoke contents which cause increase in RBCs count, Hb concentration and Hematocrit. EMCJ. January 2022; 7(1): 1-5